Renewable energy sources in spatial planning - Człowiekowska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article addresses the problem of taking renewable energy sources into account in spatial planning in Poland, especially in planning documents adopted at the level of municipalities, namely the study of conditions and directions of spatial development (after changes the structure plan) and the land use plan. It presents the conditions for specifying the location of devices (installations) based on renewable energy sources, as specified in the Polish Act on Spatial Planning and Development of 27 March 2003, as well as the fundamental principles of taking renewable energy sources into account in the planning documents adopted by municipalities.
Keywords: renewable energy sources; structure plan; land use plan; energy transition (green transition)